Hyperactive Transforming Growth Factor‐β1 Signaling Potentiates Skeletal Defects in a Neurofibromatosis Type 1 Mouse Model. (December 2013) - Rhodes, Steven D; Wu, Xiaohua; He, Yongzheng; Chen, Shi; Yang, Hao; Staser, Karl W; Wang, Jiapeng; Zhang, Ping; Jiang, Chang; Yokota, Hiroki; Dong, Ruizhi; Peng, Xianghong; et al.
ABSTRACT Dysregulated transforming growth factor beta (TGF‐β) signaling is associated with a spectrum of osseous defects as seen in Loeys‐Dietz syndrome, Marfan syndrome, and Camurati‐Engelmann disease. Intriguingly, neurofibromatosis type 1 (NF1) patients exhibit many of these characteristic skeletal features, including kyphoscoliosis, osteoporosis, tibial dysplasia, and pseudarthrosis; however, the molecular mechanisms mediating these phenotypes remain unclear. Here, we provide genetic and pharmacologic evidence that hyperactive TGF‐β1 signaling pivotally underpins osseous defects in Nf1flox/−;Col2.3Cre mice, a model which closely recapitulates the skeletal abnormalities found in the human disease. Compared to controls, we show that serum TGF‐β1 levels are fivefold to sixfold increased both in Nf1flox/−;Col2.3Cre mice and in a cohort of NF1 patients. Nf1‐deficient osteoblasts, the principal source of TGF‐β1 in bone, overexpress TGF‐β1 in a gene dosage–dependent fashion. Moreover, Nf1‐deficient osteoblasts and osteoclasts are hyperresponsive to TGF‐β1 stimulation, potentiating osteoclast bone resorptive activity while inhibiting osteoblast differentiation. These cellular phenotypes are further accompanied by p21‐Ras–dependent hyperactivation of the canonical TGF‐β1–Smad pathway. Reexpression of the human, full‐length neurofibromin guanosine triphosphatase (GTPase)‐activating protein (GAP)‐related domain (NF1 GRD) in primary Nf1‐deficient osteoblast progenitors, attenuated TGF‐β1 expression levels and reduced Smad phosphorylation in response to TGF‐β1 stimulation. As an in vivo proof of principle, we demonstrate that administration of the TGF‐β receptor 1 (TβRI) kinase inhibitor, SD‐208, can rescue bone mass deficits and prevent tibial fracture nonunion in Nf1flox/−;Col2.3Cre mice. In sum, these data demonstrate a pivotal role for hyperactive TGF‐β1 signaling in the pathogenesis of NF1‐associated osteoporosis and pseudarthrosis, thus implicating the TGF‐β signaling pathway as a potential therapeutic target in the treatment of NF1 osseous defects that are refractory to current therapies. © 2013 American Society for Bone and Mineral Research.